Sri Lanka's Migrant Labor Remittances : Enhancing the Quality and Outreach of the Rural Remittance Infrastructure - Lasagabaster, Esperanza; Maimbo, Samuel Munzele; Hulugalle, Sriyani (World Bank, Washington, DC, 2012)
Remittances-money sent home by immigrant workers abroad-are hugely beneficial to Sri Lanka. Migrants' remittances have grown dramatically in recent years and are now estimated at US$1.5 billion annually. This national phenomenon is consistent with remittance trends in neighboring countries where remittance flows are growing as rapidly. The trend is likely to continue as many workers continue to look abroad for the chance to make a better living. The economic policy implications of these trends are significant. The Sri Lankan Central Bank is now debating the following key issues: the developmental impact of remittances; the high transaction costs associated with remittances; and the level of transparency and accountability in the remittance industry, especially the informal remittance sector. This paper highlights the key policy issues associated with each of these aspects of remittances with the objective of improving the public and private infrastructure for current and future flows. Building on recent World Bank research on remittances that prominently features South Asia, it has been prepared in recognition of the development potential of these flows. It discusses some of the key issues relating to the remittance industry in Sri Lanka. This paper complements the existing literature on migrant labor remittances to Sri Lanka and extends that literature by providing specific policy-relevant guidance on short and long-term policies for enhance enhancing the quality and outreach of rural remittance infrastructure.